Digital Literacy to Improve Students' Information Evaluation and Analysis Skills in the Context of Islamic Religious Education Technology-Based at SMA Negeri 1 Raha - Rivai, Muhammad; Darsimon, Darsimon; Ilham, Ilham; B, Basir; H, Firman (International Journal on Advanced Science, Education, and Religion, 2025)
The rapid development of digital technology requires digital literacy as a crucial competency for students in navigating academic and social challenges. This study aims to analyze the influence of digital literacy on students' ability to evaluate and analyze information, particularly in the context of technology-based Islamic Religious Education at SMA Negeri 1 Raha. A quantitative approach with a correlational causality design was used, with primary data collected through a structured questionnaire administered to students. Data were analyzed using simple linear regression to determine the extent to which digital literacy predicts students' evaluative and analytical abilities. The results indicate that digital literacy significantly improves students' critical information processing abilities, particularly in assessing the credibility of religious information, distinguishing between facts and opinions, and analyzing arguments. These findings highlight that students with higher levels of digital literacy are better able to engage critically with the vast and diverse information available in the digital space. This article contributes theoretically by strengthening the role of digital literacy as a predictive factor for higher-order thinking skills, and practically by offering implications for educators and policymakers in integrating digital literacy training into the Islamic Religious Education curriculum. Additionally, this study paves the way for future research by incorporating additional variables, such as learning motivation and collaborative skills, to provide a broader understanding of how digital literacy relates to academic achievement and important learning outcomes.